Design of a elf-sustainable system based on renewable energy sources for a small museum of science dissemination - the house of silk - Maidana, Wellington (2020)
This paper presents the complete design of a selfsustainable system based on renewable energy sources - hydro and photovoltaic - for a small museum dedicated to the dissemination of science called House of Silk. The solution is based on a microgrid, connected to the main grid, using innovative technologies for energy production, storage and management. The microgrid is based on a cluster of three battery inverters which establish a three-phase supplying system. The hydro energy is generated using a low head, pico-hydro propeller turbine, connected to the microgrid through an innovative solution. The photovoltaic energy is produced by means of photovoltaic tiles and conventional modules.